Do transfer costs matter for foreign remittances? A gravity model approach - Junaid Ahmed; Inmaculada Martínez-Zarzoso (Kiel Institute for the World Economy (IfW), 2015)
Using bilateral data on remittance flows to Pakistan for 23 major host countries, in the first study of its kind, the authors examine the effect of transaction costs on foreign remittances. They find that the effect of transaction costs on remittance flows is negative and significant; suggesting that a high cost will either refrain migrant's from sending money back home or make them remit through informal channels. This can be better understood in terms of migrant networks and improvements in home and host country financial services. Distance, which has been used in previous studies as an indicator of the cost of remitting, is found to be a poor proxy.
Keywords: F22; F30; O11; 330; remittances; geographical distance; transaction cost; financial services; Pakistan